The Roles of Men in the Dating Violence Phenomenon - Jatmiko, Vivin Septiani; Avina, Diyah Ayu Amalia (Universitas Tribhuwana Tungga Dewi, 2024)
This research focuses on the roles of men discussed in the subject research papers on dating violence. Dating violence is one of the phenomena that has been drawing attention to various researchers since 1990s due to the high percentage of dating violence cases in various countries and the negative effects it has caused to the involved parties. The selected research articles were analysed using systematic literature review (SLR) by using PRISMA Diagram. According to the analysis, a discourse may have implications in forming power, which, in turn, may lead to blinding knowledge. This research finds that the dominant discourse exists in most of the selected research papers, where men being positioned as offenders in dating violence incidents. The emergence of the dominant discourse is attributed by the presence of controls on the institutions (publishers). The influence of controls can be seen in the positioning of men portrayed as masculine, dominant, and rough by the majority of the journal editorial boards and authors; such a framing may form the dominant course in that particular type of research. Furthermore, the massive usage of quantitative research in the dating violence topic is seen as further forming a single fact. In essence, the dominant course results in the silent majority, a condition where male victims are reluctant to seek help from police authority or their social community on their violence cases.